Gap and opportunity analysis of hydrological monitoring in the Ziway-Shala Sub-basin, Ethiopia - Donauer, T.; Haile, Alemseged Tamiru; Goshime, Demelash Wondimagegnehu; Siegfried, T.; Ragettli, S. (International Water Management Institute, 2020)
This working paper was prepared under a development and conservation project – Societal Development and Ecosystems Conservation in Sahelian Wetlands (SAWEL) – focusing on improving food security and nutrition in the Sahel region by helping to safeguard wetlands through ecologically sustainable agricultural water management. SAWEL is supported by the Swiss Agency for Development and Cooperation (SDC). This paper provides an overview of the current situation with regards to hydrological monitoring in the Ziway-Shala sub-basin in the Central Rift Valley of Ethiopia, including details of existing river and lake gauging stations in the sub-basin. The study was jointly conducted by the International Water Management Institute (IWMI) and Hydrosolutions through consultation with staff of the Rift Valley Lakes Basin Development Office (RVLBDO), field trips to gauging stations, inspection of data recording books and reviewing previous studies. In addition to highlighting gaps in hydrological monitoring in the Ziway-Shala sub-basin, opportunities (e.g., remote sensing and citizen science) for novel, non-traditional hydrological monitoring are also presented.